Software as a Service: Design and Build Lower Usage Cost Email Marketing for Hospitality Industry - Sukarsa, I Made; Buana, Putu Wira; Arynasta, I Putu Krisna (Scientific Journal of Informatics, 2020)
The hospitality industry is an industry that is very customer-focused because it relies on customer information. Therefore, Customer Relationship Management (CRM) is implemented worldwide in this sector. Many features of CRM applications that are often not suitable for use by small and medium companies also make features in CRM applications tend to be wasteful. This paper aims to develop a software as a service CRM with lower usage costs without imposing development costs on users and focuses on email marketing features and data exchange integration. The system development uses the SDLC (System Development Life Cycle) method. Testing in this paper was conducted with User Acceptance Testing (UAT) where managers or hotel owners and students in the field of information technology use the application system then provide an assessment through a questionnaire. The total score obtained from 30 respondents is 1233 and be on point between the Quartile III (1200) and the Maximum score point (1500) base on LSR interpretation scaling and showed the system is considered positive and successful. The conclusion of this study is the application system can be used by hoteliers in the hospitality industry at various levels of the company to carry out functions that support customer relationship management and email marketing.